1998
DOI: 10.1021/jp980315p
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Investigation of Various States of the Molecules TcC, TcC2, ScC2, and YC2

Abstract: Spin-polarized density functional theory has been used to investigate the C 2V , C ∞V and D ∞h isomers of the molecules MC 2 , M ) Sc, Y, Tc, and selected states of the diatomic molecule TcC. According to the theory, the ground state of the diatomic is the 4 Σ + TcC isomer. Bond length comparisons between the doublet and quartet isomers reveal the ground state has a double bond, and the first excited state ( 2 ∆ TcC) is triple bonded. For MC 2 , M ) Sc, Y, Tc, numerous minima were located, including spin state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 38 publications
5
25
1
1
Order By: Relevance
“…[2]- [5], using the case b βJ basis set, |N K S J I F . This basis corresponds to the vector coupling N + S = J; J + I = F. [8] The rotational and hyperfine matrix elements in this basis have been given by Refs. (23)(24)(25).…”
Section: Determination Of the Rotational And Hyperfine Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2]- [5], using the case b βJ basis set, |N K S J I F . This basis corresponds to the vector coupling N + S = J; J + I = F. [8] The rotational and hyperfine matrix elements in this basis have been given by Refs. (23)(24)(25).…”
Section: Determination Of the Rotational And Hyperfine Constantsmentioning
confidence: 99%
“…Jackson et al (8) performed a spin-polarized density functional calculation which gave the ground state structure as r e (Y-C) = 2.223Å, r e (C-C) = 1.277Å, C-Y-C = 33.2…”
mentioning
confidence: 99%
“…10 Because of the difficulties of the theoretical treatment of even moderately sized M-C systems, attention has been focused on small M-C clusters in the hope that they will provide insight into M-C cluster growth mechanisms and the possible building blocks of the larger mixed species. So far, studies have found no difference between early and late 3d metals as regards the structures of monometallic di-and tri-carbides: MC 2 clusters (MϭSc, Ti, V, Fe, Co, and Ni͒ are isosceles triangles in the ground state, [11][12][13][14][15][16][17][18][19][20][21][22][23] and MC 3 clusters (MϭSc, Ti, V, Cr, Mn, Fe and Ni͒ have two-dimensional ''fan'' structures in which the M atom is bound to all three C atoms and the latter are bound together in a bent chain. 17,24 -26 Moreover, although in principle the early or late character of each M is expected to be more clearly manifested by dimetallic carbide clusters, extensive studies of M 2 C 2 clusters (MϭTi, V, and Co͒ using density-functional theory ͑DFT͒ have found no clear early-late difference: the ground-state geometries of V 2 C 2 and Co 2 C 2 , and the Ti 2 C 2 isomer of second-lowest energy, are all planar rings with transannular M-C bonds, [27][28][29] although ground-state Ti 2 C 2 is a planar ring with a transannular C-C bond.…”
Section: Introductionmentioning
confidence: 99%
“…Monometallic dicarbide clusters, MC 2 (MϭSc, Ti, V, Fe, Co, and Ni͒, have been studied, [10][11][12][13][14][15][16][17][18][19][20][21][22] and are found to have similar isosceles triangular structures in common, where a metal atom is bound to a carbon dimer unit by a relatively strong ionic interaction. The individual character of each transition metal is not discernible in the simplest carbides, MC 2 , but is expected to be manifested in its dimetallic carbide cluster, M 2 C n .…”
Section: Introductionmentioning
confidence: 99%